2018
DOI: 10.1017/s1431927618015453
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Two Combined Oral Contraceptives Containing Ethinyl Estradiol and Drospirenone on Whole Blood Clot Viscoelasticity and the Biophysical and Biochemical Characteristics of Erythrocytes

Abstract: Venous thrombosis is associated with combined oral contraceptive (COC) use. We investigated the impact of two ethinyl estradiol (EE) and drospirenone (DRSP) containing COCs (3 mg DRSP/20µg EE and 3µg DRSP/30µg EE) on the viscoelasticity of whole blood clots along with the biophysical and biochemical characteristics of erythrocytes. Thromboelastography (TEG) analysis showed a tendency toward a hypercoagulable state in the COCs groups that was more pronounced with higher EE concentrations. Light microscopy and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 62 publications
(79 reference statements)
2
21
0
4
Order By: Relevance
“…It appears that the presence of red blood cells and platelets, therefore, masked the true effect of these hormones on the coagulation factors, specifically fibrin. Spontaneous fibrin formation observed with SEM analysis of whole blood, however, indicated that the fibrin component was, in fact, significantly affected (Emmerson et al, 2018), emphasizing the need for a multidisciplinary approach when investigating coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It appears that the presence of red blood cells and platelets, therefore, masked the true effect of these hormones on the coagulation factors, specifically fibrin. Spontaneous fibrin formation observed with SEM analysis of whole blood, however, indicated that the fibrin component was, in fact, significantly affected (Emmerson et al, 2018), emphasizing the need for a multidisciplinary approach when investigating coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…When we examined the whole blood viscoelasticity of this same cohort of DRSP/EE female users, only three parameters showed significant results, namely the R, α , and TMRTG. DRSP/30EE showed the greatest variation in these, indicating that the higher EE concentration had the greatest influence on the initiation time as well as the rate at which the thrombus forms due to an increase in the thrombin burst (Emmerson et al, 2018). On the other hand, the majority of the viscoelastic parameters were significantly influenced by DRSP/EE use in the PPP samples, with the lowest dose having the greatest effect; this indicates that the fibrin component is severely affected by these hormone formulations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Следовательно, комбинация дроспиренона и ЭЭ влияет на биофизические и биохимические свойства эритроцитов, вызывая переход гемостаза в протромботическое состояние. Хотя выявленные эффекты в основном являются субклини ческими, долгосрочные эффекты и риски, связанные с использованием этих гормонов, должны тщательно рассмат риваться для каждой женщины [38].…”
Section: влияние гестагенов на параметры коагуляцииunclassified